Peripheral Neutrophil Functions and Cell Signalling in Crohn`s Disease - Somasundaram, Rajesh; Nuij, Veerle J. A. A.; van der Woude, C. Janneke; Kuipers, Ernst J.; Peppelenbosch, Maikel P.; Fuhler, Gwenny M. (PloS one, 2013)
The role of the innate immunity in the pathogenesis of Crohn's disease (CD), an inflammatory bowel disease, is a subject of increasing interest. Neutrophils (PMN) are key members of the innate immune system which migrate to sites of bacterial infection and initiate the defence against microbes by producing reactive oxygen species (ROS), before undergoing apoptosis. It is believed that impaired innate immune responses contribute to CD, but it is as yet unclear whether intrinsic defects in PMN signal transduction and corresponding function are present in patients with quiescent disease. We isolated peripheral blood PMN from CD patients in remission and healthy controls (HC), and characterised migration, bacterial uptake and killing, ROS production and cell death signalling. Whereas IL8-induced migration and signalling were normal in CD, trans-epithelial migration was significantly impaired. Uptake and killing of E. coli were normal. However, an increased ROS production was observed in CD PMN after stimulation with the bacterial peptide analogue fMLP, which was mirrored by an increased fMLP-triggered ERK and AKT signal activation. Interestingly, cleavage of caspase-3 and caspase-8 during GMCSF-induced rescue from cell-death was decreased in CD neutrophils, but a reduced survival signal emanating from STAT3 and AKT pathways was concomitantly observed, resulting in a similar percentage of end stage apoptotic PMN in CD patients and HC. In toto, these data show a disturbed signal transduction activation and functionality in peripheral blood PMN from patients with quiescent CD, which point toward an intrinsic defect in innate immunity in these patients.